Ovarian torsion occurring nine days after ipsilateral dermoid cystectomy - Pauline Chang (Wolters Kluwer Medknow Publications, 2021)
Ovarian torsion (OT) is a gynecological emergency that requires prompt treatment and management. It is associated with risk factors such as ovarian cysts and prior pelvic surgery. Diagnosis and treatment require surgery to examine the adnexa, correct the torsion, and determine if cystectomy or oophorectomy are required. We reported the case of a 34-year-old woman who presented 9 days after a dermoid cystectomy with sudden onset abdominal pain. An ultrasound showed abnormal blood flow to the ovary. She then underwent a repeat laparoscopy revealing a necrotic and twisted ovary on the same side that had a cystectomy. The surgeons proceeded with a right oophorectomy. Following surgery, the patient reported no concerns with no ongoing bleeding or pain. OT can present in the short-term postoperatively to an ovarian cystectomy, likely as a result of mechanical forces secondary to structural changes of the ovary. The role for prophylaxis against OT is unclear in those with significant risk factors for torsion.